A review on the essential role of substrate on aerobic granulation. (6th December 2010) - Yang, Fenglin; Wang, Xinhua; Zhang, Hanmin; Wang, Yongfei, Mingming Gao
Aerobic granulation is a selection pressure-driven cell-to-cell immobilisation process. So far, the essential role of substrates on aerobic granulation has not been well clarified. This paper reviews current studies about aerobic granulation with different substrates. Although substrates do not exert a major selection pressure on aerobic granulation, they will select substrate-related microorganisms and adjust microbial diversity, and further influence the formation, stability, and structure of aerobic granules. Co-substrate cultivation strategy can be adopted to accelerate aerobic granulation and improve the stability and performance of aerobic granules. This paper hopes to provide a platform for developing full-scale aerobic granules based bioreactors.